UKRAINIAN SCIENTISTS AND THE BEGINNING OF THE NATIVE METEORITICS - Eremeeva, A. I. (Одеські астрономічні публікації, 2017)
The oldest known meteorite on the Ukraine territory fallen in 1787y. played essential part on the first stage of the native meteoritics development. The Kharkov university professors were ones of the first who investigated this meteorite in the beginning of XIXc. Prof. A.I.Stoikovich was the first author of the fundamental book on the aerolithes problem in Russia. P.Ya.Gamaleya (from Poltava province) was the first in Russia who believed the asteroid nature for the aerolithes and the shooting stars.